Advances in pharmacogenomics for personalized emergency medicine: Implications for drug safety and efficacy - Alammar, Fatimah Abdullah; Alghamdi, Abeer Saleh; Almuhaylib, Abdulaziz Mohammed; Alotaibi, Suhoud Saud; Alwaked, Mohammed Hamoud; Alrashidi, Abdulaziz Ahmad; Alrasheedi, Bander Batti; Alsarimi, Fayez Abdullah Hussain; Alanazi, Amani Ayyadhah; Alumtairi, Adel Zayed (International journal of health sciences, 2023)
Background: Advances in pharmacogenomics are transforming personalized emergency medicine by addressing genetic variability in drug metabolism and response. Genetic variations can significantly affect drug safety and efficacy, particularly in emergency scenarios where rapid and effective treatment is critical. Aim: This review aims to explore how pharmacogenomics can enhance personalized emergency medicine, focusing on implications for drug safety and efficacy. Methods: We reviewed recent literature on pharmacogenomics, emphasizing its impact on drug responses in various clinical contexts including chronic diseases, autoimmune disorders, cancer, infectious diseases, psychiatric and neurologic conditions, and chronic pain. The review included case studies and clinical guidelines that integrate genetic testing into drug prescribing practices. Results: Pharmacogenomic research has identified numerous genetic variations influencing drug metabolism and efficacy. For instance, variations in genes such as CFTR, TPMT, BRCA1/2, and UGT1A1 can predict drug responses and adverse reactions, leading to more tailored and effective treatments. Implementation of pharmacogenomic testing has demonstrated potential in reducing adverse drug reactions and improving therapeutic outcomes across several conditions, including cystic fibrosis, cancer, and chronic pain. Conclusion: Incorporating pharmacogenomic data into emergency medicine practice offers significant benefits by personalizing treatment plans and minimizing adverse effects.